Histological and Ultrastructural Studies on the Hassall’s Corpuscles of Kadaknath Fowl - Panwar, V.S. (Indian Journal of Veterinary Anatomy, 2020)
Histological and Transmission Electron Microscopic studies were conducted in the Hassall’s corpuscles found in the thymus of 25 Kadaknath fowls of different age groups. During the study Kadaknath birds from day old to thirty weeks of age were reared in college poultry farm. These birds were sacrificed ethically and small pieces of thymic lobules were collected in neutral buffered formalin for histological and in 2.5% glutaraldehyde solution in 0.05M phosphate buffer at pH 7.2 for ultra structural studies.The Hassall’s corpuscles appeared at second week of age in birds and there was no regression of the thymus up to twenty six weeks of age. The Hassall’s corpuscles had hyalinized center and peripheral concentrically arranged epithelial reticular cells. In the present study, two types of Hassall’s corpuscles were seen as type-I flattened reticuloepithelial cells, which were arranged in concentric manner around the acidophilic central cornified mass whereas type-II Hassall’s corpuscles were spherical in shape encircled by flattened reticuloepithelial cells, enclosing a hyaline mass witha group of cells. The number of Hassall’s corpuscles increased with the advancement of age in Kadaknath fowl. Due to this fact the Kadaknath birds were more disease resistant in early ages.